Russia's quest for influence in Africa after the 2022 Ukraine invasion: Instruments, causes and consequences - Elias Götz; Jonas Gejl Kaas (Danish Institute for International Studies (DIIS), 2024)
This report offers an analysis of Russia's Africa policy since its February 2022 invasion of Ukraine. Three major conclusions emerge from it. First, Russia is engaged in a concerted effort to maintain and, if possible, extend its politico-military influence on the continent. To this end, it employs a range of relatively cheap but effective policy instruments. These include the provision of security assistance, weapons transfers, information operations and diplomatic levers. Second, the primary drivers, or sources, of Russia's influence-seeking policy can be attributed to aspirations of great power status, geopolitical considerations and commercial interests. Third, Russia has been able to convert its activism on the continent into political influence, at least to some extent. This is shown through an analysis of Moscow's impact upon African states' voting behaviour in the UN General Assembly. At the same time, it also becomes clear that Russia's influence is not limitless; on the contrary, it is heavily conditioned by regional dynamics and local factors.
Keywords: 300; Africa; Russia; politico-military influence; geopolitical consideration; UN General Assembly; Ukraine; the West; voting behavior